Short term effect of non-surgical periodontal treatment on chemokine momocyte chemoattrant protein-3 in patients with chronic periodontitis - Asma Mohamed Serag Edien Rabie; Mona Shoeib; Naglaa M. Elwakeel (Cairo : Asma Mohamed Serag Edien Rabie, 2013)
Objective: The aim of the present study was to assess the diagnostic value of MCP-3 in periodontal diseases by: Determining the concentration of MCP-3 in GCF from active sites of periodontal destruction in patients suffering from chronic periodontitis as copared to normal control patients. Comparing between MCP-3 levels in GCF samples from active sites before and after supragingival and subgingival debridment
Thesis (M.Sc.) - Cairo University - Faculty of Oral and dental Medicine - Department of Periodontology
Issued also as CD
Keywords: Chemokines; MCP-3; Periodontal disease